Rapid decline of HIV-1 DNA and RNA in infants starting very early antiretroviral therapy may pose a diagnostic challenge. (13th March 2018) - Veldsman, Kirsten A.; Maritz, Jean; Isaacs, Shahieda; Katusiime, Mary G.; Janse van Rensburg, Anita; Laughton, Barbara; Mellors, John W.; Cotton, Mark F.; van Zyl, Gert U.
Abstract : Objective: Birth diagnosis of HIV-1 infection offers an ideal opportunity for early antiretroviral therapy (ART) to limit HIV-1 reservoir size and limit disease progression. Although data on cellular HIV-1 DNA decay exist for children commencing treatment from 2 to 3 months of age, data are lacking for starting shortly after birth. Design: We studied infants who initiated ART within 8 days after birth to assess HIV-1 DNA levels longitudinally. Methods: Children were recruited from public health clinics in Cape Town where birth diagnosis of HIV-1 coupled with early ART initiation occurred. Total cellular HIV-1 DNA levels were determined using a sensitive quantitative PCR targeting a conserved region in integrase . Results: Of 11 infants diagnosed and beginning ART within 8 days of birth with detectable pre-ART HIV-1 DNA, three subsequently had undetectable HIV-1 DNA after 6 days, 3 months and 4 months on treatment, respectively. In seven who had virologic suppression (defined as a continuous downward trend in plasma HIV-1 RNA, and <100 copies/ml after 6 months) total HIV-1 DNA continued to decay over 12 months [mean half-life of 64.8 days (95% confidence interval: 47.9–105.7)]. Conclusion: In infants initiated on ART within 8 days of life the combination of maternal ART, and early ART for prophylaxis and treatment contribute to rapid decline of HIV-1 infected cells to low or undetectable levels. However, rapid decline of HIV-1 RNA and DNA may complicate definitive diagnosis when confirmatory testing is delayed. Abstract : Supplemental Digital Content is available in the text